Obesity Progression Between Young Adulthood and Midlife and Incident Arthritis: A Retrospective Cohort Study of US Adults. Issue 3 (25th February 2021) - Berry, Kaitlyn M.; Neogi, Tuhina; Baker, Joshua F.; Collins, Jason M.; Waggoner, Jason R.; Hsiao, Chia‐Wen; Johnston, Stephen S.; LaValley, Michael P.; Stokes, Andrew C.
Abstract : Objective: To examine the association between weight change from young adulthood to midlife and the risk of incident arthritis. Methods: Using data from the National Health and Nutrition Examination Survey, we categorized participants into weight‐change categories based on their recalled weight during young adulthood and midlife. We estimated the association of weight change and developing an arthritis condition over 10 years using adjusted Cox models. Findings were extrapolated to the US population to determine the proportion of incident arthritis cases that could be averted if the entire population maintained a normal body mass index (BMI) in young adulthood and midlife. Results: Among our sample of adults who were ages 40–69 years at their midlife weight measure (n = 13, 669), 3, 603 developed an arthritis condition. Compared with adults who maintained a normal–normal BMI, the normal–overweight, normal–obese, overweight–obese, and obese–obese groups had a significantly elevated risk of incident arthritis conditions. The obese–overweight group had a lower risk of incident arthritis conditions compared with the obese–obese group and a comparable risk to the overweight–overweight group. Nearly one‐fourth of incident arthritis cases, corresponding to 2.7 million individuals, would have been averted under the hypothetical scenario where all individuals maintained normal weight from young adulthood to midlife. Conclusion: Weight loss from young adulthood to midlife was associated with a substantially reduced risk of developing an arthritis condition. We found no evidence of residual risk from having been heavier earlier in life. Our findings highlight the critical need to expand obesity treatment and prevention to achieve meaningful reductions in the burden of arthritis.